2021
DOI: 10.3390/app11167242
|View full text |Cite
|
Sign up to set email alerts
|

Volume and Distribution of Periprosthetic Bone Cysts in the Distal Tibia and Talus before Early Revision of Total Ankle Arthroplasty

Abstract: Periprosthetic osteolysis is a common complication following total ankle arthroplasty (TAA). However, understanding of osteolysis volume and distribution is still evolving, undermining efforts to reduce the incidence of osteolysis via bone remodeling. We obtained data on the characteristics of osteolysis developing within the distal tibia and talus after TAA. Three-dimensional computed tomography (3D-CT) reconstructions of 12 patients who underwent HINTEGRA TAA were performed. We identified 27 volumes of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These are caused by talar facets variations in terms of shape and orientation [27]. Another study reported prevalence of medial and lateral extension of 11% and 8% respectively [28]. Medial extension was seen in 61% cases as reported by Al-Jabri et al [29].…”
Section: Discussionmentioning
confidence: 89%
“…These are caused by talar facets variations in terms of shape and orientation [27]. Another study reported prevalence of medial and lateral extension of 11% and 8% respectively [28]. Medial extension was seen in 61% cases as reported by Al-Jabri et al [29].…”
Section: Discussionmentioning
confidence: 89%
“…However, besides additional bone loss, it may convert the bone-implant interface along its stem to vertical shear forces. Furthermore, delayed or missing osseointegration can result in subsidence and further bone loss [15][16][17] . Alternatively, the use of bone cement has been proposed and may be critical for younger patients 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In cases of large ballooning cyst formation and progressive bone loss including the malleoli, it is worth considering whether the reconstruction of the bony structures enables sufficient osseointegration of the revised standard components or whether other salvage options, such as arthrodesis or use of intramedullary fixation, are required. However, the latter may carry an increased risk of further bone loss and debilitating loss of function 10,[13][14][15][16][17][18] .…”
mentioning
confidence: 99%